Preserved learning during the Symbol Digit Substitution Test in patients with schizophrenia, age-matched controls and elderly - Cornelis, Claudia; De Picker, Livia J.; Hulstijn, Wouter; Dumont, Glenn; Timmers, Maarten; Janssens, Luc; Sabbe, Bernard G.; Morrens, Manuel (Frontiers in Psychiatry, 2015)
Objective: Speed of processing, one of the main cognitive deficits in schizophrenia is most frequently measured with a digit symbol-coding test. Performance on this test is additionally affected by writing speed and the rate at which symbol-digit relationships are learned, two factors that may be impaired in schizophrenia. This study aims to investigate the effects of sensorimotor speed, short-term learning and long-term learning on task performance in schizophrenia. In addition the study aims to explore differences in learning effects between patients with schizophrenia and elderly individuals. Methods: Patients with schizophrenia (N=30) were compared with age-matched healthy controls (N=30) and healthy elderly volunteers (N=30) during the Symbol Digit Subsstitution Test (SDST). The task was administered on a digitizing tablet, allowing precise measurements of the time taken to write each digit (writing time) and the time to decode symbols into their corresponding digits (matching time). The SDST was administered on three separate days (day 1, day 2, day 7). Symbol-digit repetitions during the task represented short-term learning and repeating the task on different days represented long-term learning. Results: The repetition of the same symbol-digit combinations within one test and the repetition of the test over days resulted in significant decreases in matching time. Interestingly, these short-term and long-term learning effects were about equal among the three groups. Individual participants showed a large variation in the rate of short-term learning. In general, patients with schizophrenia had the longest matching time whereas the elderly had the longest writing time. Writing time remained the same over repeated testing. Conclusion: The rate of learning and sensorimotor speed were found to have a substantial influence on the SDST score. However, large individual variation in learning rate should be taken into account in the interpretation of task scores for